Case Report: Sclerosing variant of extramedullary hematopoietic tumor primary arising in kidney, unexpected clinical and pathological presentation - Haneen Al-Maghrabi; Ghadeer Mokhtar; Feras Asali; Abdelrazak Meliti (Frontiers in Oncology)
Extramedullary hematopoiesis (EMH) is a physiological process that occurs outside the bone marrow, often in response to various hematological conditions. The sclerosing variant of EMH in the kidney is a rare manifestation characterized by the proliferation of hematopoietic cells within the renal interstitium, accompanied by significant fibrous tissue formation. This report presents a case of a patient with chronic myelofibrosis who exhibited the sclerosing variant of EMH. Imaging studies revealed renal masses, which were initially misinterpreted as malignant lesion. Histopathological examination of the renal tissue demonstrated a marked increase in hematopoietic cell types, including myeloid and erythroid lineages, interspersed with abundant collagenous stroma indicative of sclerosis. The clinical implications of this variant are noteworthy, as it may mimic renal tumors and lead to unnecessary surgical interventions. Understanding the histopathological characteristics and clinical context of sclerosing EMH in the kidney is crucial for accurate diagnosis and management. This case underscores the importance of considering EMH in the differential diagnosis of renal masses, particularly in patients with underlying hematological disorders or chronic renal conditions. Further research is needed to elucidate the pathophysiological mechanisms driving this variant and its potential implications for renal function and overall patient outcomes.